2017
DOI: 10.1002/ijc.30823
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocytes repress hepatic tumorigenesis but not development in Hras12V transgenic mice

Abstract: Increasing reports show noninflammation underlying HCC, challenging our understanding of the roles of the immune system in hepatocarcinogenesis. By exploring a mouse model of hepatic tumor induced by hepatocyte-specific expression of the Hras12V oncogene without obvious inflammation, we found that the proportion of B cells, but not T cells, progressively and significantly decreased in 3, 5-month-old transgenic mice (Tg) compared with non-transgenic mice. Notably, the proportions of total and activated B and T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…For example, by exploring Ras‐Tg mice, we found that differences in the molecular responses to the deregulated Ras oncoprotein between females and males determine the onset of HCC, which may contribute to the striking male prevalence of HCC . In addition, we and other researchers found that B lymphocytes, FoxM1, and miR‐221 play crucial roles in HCC by using Ras‐Tg mice .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…For example, by exploring Ras‐Tg mice, we found that differences in the molecular responses to the deregulated Ras oncoprotein between females and males determine the onset of HCC, which may contribute to the striking male prevalence of HCC . In addition, we and other researchers found that B lymphocytes, FoxM1, and miR‐221 play crucial roles in HCC by using Ras‐Tg mice .…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, the hyperactivation of the MEK/ERK and PI3K/AKT/mTOR signaling pathways was a marked molecular event in HCC . Reports based on the Ras‐Tg mouse demonstrate that it is a valuable model to investigate molecular mechanisms, diagnosis and therapeutic strategies, and biomarkers of hepatocarcinogenesis . For example, by exploring Ras‐Tg mice, we found that differences in the molecular responses to the deregulated Ras oncoprotein between females and males determine the onset of HCC, which may contribute to the striking male prevalence of HCC .…”
Section: Introductionmentioning
confidence: 89%
“…Depletion of B cells by an anti-CD20 antibody in a syngeneic HCC mouse model or inactivation of B cells in Hras12V Tg mice using a Bruton's kinase inhibitor enhanced HCC growth. 67,68 By contrast, an Mdr2 À/À mouse model of HCC, mice treated with anti-CD20 antibody and B cell-deficient mice showed reduced inflammation-associated HCC. 69 Levels of immunoglobulin A (IgA)-producing plasma cells converted from IgM-producing B cells were increased in human NASH livers and in mouse models of NASH-promoted HCC, including HFD-fed major urinary protein-urokinase type plasminogen activator (MUP-uPA) mice and HFD-fed streptozotocin-treated mice, but not in the HFD plus DEN model of HCC.…”
Section: Adaptive Immunity Has Anti-and Protumorigenic Roles In Hccmentioning
confidence: 97%
“…A similar phenomenon has also been observed in liver disease. In a Hras12V HCC mouse models, B cells were found to have a potential role in suppressing hepatic tumorigenesis (Wang et al, 2017), whereas in another mouse model with inflammation-associated HCC, infiltrating B cells was correlated with increased tumor aggressiveness and mortality (Faggioli et al, 2018). In addition, activated FcγRII low/− B cells from HCC tumor may also suppress host anti-tumor immune response via IL-10 signals (Ouyang et al, 2016;Jin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%